(untitled) (Research, Society and Development, 2020)
The analysis of the complaints allows us to assess the population’s knowledge about health risks and the role of health surveillance as a public health promotion agent. It is a fundamental tool for a holistic view of the health risks found in the municipality. The objective of the present study was to analyze the complaints received by the health surveillance during the period of 12 months. The complaints were classified according to the related area in food trade, health establishments, medicines and health establishments. They were also grouped according to the problem reported in: damaged/expired products, poor hygiene, wastewater, irregular services, lack of sanitary permit, presence of animals/insects. The conclusion of the sanitary inspection was classified as unfounded, well founded, partially well founded. The complaints received by the sanitary surveillance in the city of Rio Grande - RS, mostly were in the area of food trade and establishments of interest to health, among the problems that led to the motivation of reporting damaged/expired products and poor hygiene. more frequently and most of the complaints led to action by the inspectors to reduce health risks.